Cross-Jurisdictional Resource Sharing in Local Health Departments: Implications for Services, Quality, and Cost - Humphries, Debbie L.; Hyde, Justeen; Hahn, Ethan; Atherly, Adam; O’Keefe, Elaine; Wilkinson, Geoffrey; Eckhouse, Seth; Huleatt, Steve; Wong, Samuel; Kertanis, Jennifer (Frontiers in Public Health, 2018)
Background Forty one percent of local health departments in the U.S. serve jurisdictions with populations of 25,000 or less. Researchers, policymakers, and advocates have long questioned how to strengthen public health systems in smaller municipalities. Cross-jurisdictional sharing may increase quality of service, access to resources, and efficiency of resource use. Objective To characterize perceived strengths and challenges of independent and comprehensive sharing approaches, and to assess cost, quality, and breadth of services provided by independent and sharing health departments in Connecticut (CT) and Massachusetts (MA). Methods We interviewed local health directors or their designees from 15 comprehensive resource-sharing jurisdictions and 54 single-municipality jurisdictions in CT and MA using a semi-structured interview. Quantitative data were drawn from closed-ended questions in the semi-structured interviews; municipal demographic data were drawn from the American Community Survey and other public sources. Qualitative data were drawn from open-ended questions in the semi-structured interviews. Results The findings from this multistate study highlight advantages and disadvantages of two common public health service delivery models – independent and shared. Shared service jurisdictions provided more community health programs and services, and invested significantly more (120 per thousand (1K) population vs. 69.5/1K population) on healthy food access activities. Sharing departments had more indicators of higher quality food safety inspections (FSIs), and there was a non-linear relationship between cost per FSI and number of FSI. Minimum cost per FSI was reached above the total number of FSI conducted by all but four of the jurisdictions sampled. Independent jurisdictions perceived their governing bodies to have greater understanding of the roles and responsibilities of local public health, while shared service jurisdictions had fewer staff per 1,000 population. Implications There are trade-offs with sharing and remaining independent. Independent health departments serving small jurisdictions have limited resources but strong local knowledge. Multi-municipality departments have more resources but require more time and investment in governance and decision-making. When making decisions about the right service delivery model for a given municipality, careful consideration should be given to local culture and values. Some economies of scale may be achieved through resource sharing for municipalities <25,000 population.